Evolution and prospect of 5GtoB application in China - Feng PAN; Jiawei LIU (Dianxin kexue)
5G convergence application is the key support for the digital development of China's economy and society.After more than two years of development, China's 5GtoB application has accelerated to bloom, has achieved a breakthrough from 0 to 1, and the enabling effect is obvious.The development of 5GtoB application needs to be further promoted from three directions: strengthening network supply, reducing application threshold and building application industry ecology.It is believed that in the future, 5GtoB applications will continue to develop and promote the wireless economy to become an important part of China's national economy.